Teaching about burnings in a rural school in the country side of Minas Gerais State: a case study (Research, Society and Development, 2018)
Burns are considered to be environmental crimes and occur in the form of out-of-control fires, especially in lands, forests and forests that occur in the world and in Brazil, destroying vegetation, degrading the environment and often harming the health of people in the region. which they occur. Statistics point to an increase in the number of such offenses. The purpose of this article is to present a case study of rural school burnout that has minimized the reported cases of this practice. A qualitative social research is carried out in which the work on burnings and reports of students and teachers is verified. There is every reason to believe that work together with schools is one of the most effective and long-term ways to reduce the number of burnings in our country.